Postcard sent to Luce Fabbri. Text on the back: "Para la querida Luce, Conce" Buenos Aires 4-14-1947
Postcard sent to Luce Fabbri. Text on the back: "Para la querida Luce, Conce" Buenos Aires 4-14-1947.